(untitled) (European Journal of Pure and Applied Mathematics, 2025)
This article considers a new class of generalized Bell-based Frobenius-type Eulerian polynomials of two variables. Also, diverse properties and formulae for these new polynomials are investigated and analyzed. Then, some symmetric identities and implicit summation formulae are improved. The stack of zeros and surface representations of generalized Bell-based Frobenius-type Eulerian polynomials are given for some particular values of the parameters.